Current characteristics of ichthyofauna of the channel «Dnieper–Donbass» - Новіцький, Р. О.; Кочет, В. М.; Христов, О. О.; Кузора, В. Є. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
In 2014 comprehensive studies of the fish fauna of four sites of the channel «Dnieper–Donbass» were conducted. 26 species of fish were recorded. Almost all the registered species belong to limnophilic ecological complexes, 3 species are rheophils. There is a clear positive effect of the protection of aquatic biological resources of the channel. Within the boundaries of all the studied sites there have been revealed an optimized development and formation of stable populations of native fish of the region. There is a powerful biomelioration effect from the invasion of herbivorous fish species. The data obtained indicate the significant bioproduction potential of the channel.